(untitled) (Nigerian Journal of Cooperative Economics and Management, 2026)
This study examined the effect of ICT-driven loan tracking and repayment systems on the operational efficiency of credit cooperative societies in Onitsha South Local Government Area, Anambra State, Nigeria. Specifically, the study investigated the influence of digital loan tracking systems, repayment monitoring mechanisms, and reminder systems on operational efficiency. A descriptive survey research design was adopted. The population comprised 133 respondents drawn from selected credit cooperative societies, of which 121 valid questionnaires were retrieved and analyzed. Data were collected using a structured questionnaire based on a 5-point Likert scale and analyzed using descriptive statistics and Multiple Regression Analysis. The findings revealed that digital loan tracking systems significantly improve operational efficiency through enhanced loan administration, record management, and service delivery. Repayment monitoring mechanisms positively influenced operational efficiency by improving repayment compliance and reducing loan defaults. Similarly, reminder systems significantly enhanced operational efficiency by promoting timely loan repayment and strengthening loan recovery processes. The study concluded that ICT-driven loan tracking and repayment systems contribute significantly to improved loan management practices and operational efficiency. It recommended increased adoption of ICT-based loan management systems and effective repayment monitoring strategies to enhance the performance and sustainability of credit cooperative societies.